Chinese quince (Chaenomeles sinensis) seed gum: Structural characterization. (February 2018) - Wang, Li; Liu, Hua-Min; Xie, Ai-Jun; Wang, Xue-De; Zhu, Chun-Yan; Qin, Guang-Yong
Abstract: Chinese quince seed gum (CQSG) is a novel potential viscosifier or stabilizer with good storage stability. In this work, CQSG was extracted from the surface of Chaenomeles sinensis (Chinese quince) seeds, and purified by DEAE-Sepharose Fast-Flow and Sephacryl S-400 HR chromatography; three fractions were obtained (CQSG-1, -2, -3). The main fraction (CQSG-2) was investigated by monosaccharide analysis, methylation and one-dimensional (1D) and two-dimensional (2D) nuclear magnetic resonance (NMR) experiments to determine its structure. Results showed that CQSG-2 is composed of arabinose (Ara), glucose (Glu), xylose (Xly), galacturonic acid (Gala) and glucuronic acid (Glua) in a molar ratio of 4.0:0.3:15.2:4.2:3.8. →4-β-d -Xyl p -1→ and →2, 4-β-d -Xyl p -1→ constitute the backbone in a ratio of 5.9:4.5, and the Ara p -1→, α-d -Gal p A-1→, →2-α-d -Glc p A-1→, →4-β-d -Glc p -1→, and →2, 3, 5-l -Ara f -1→ form the branched chain. The molecular aggregation of CQSG-2 with high molecular weight (Mw) (1.4 × 10 6 Da) was strong compared with CQSG-1 and CQSG-3. This is the first systematic elucidation of the structure of Chinese quince seed gum, and it provides the basis for developing applications for this gum in the food and pharmaceutical industries. Graphical abstract: Highlights: The storage stability of preliminarily purified CQSG was good. Ara, Glu, Xly, Gala and Glua exist in the main fraction of CQSG. The fine structure of the main fraction was characterized by methylation, 1D/2D NMR spectra. The main fraction of CQSG was composed mainly of →4-β-d -Xyl p -1→ and →2, 4-β-d -Xyl p -1→. The results are of interest to the manufacturing of the pharmaceuticals and foods.